The Revitalization of Regional Literature as a Strategy to Improve Writing Ability and Reproducing Literature - Arinah Fransori (Journal La Edusci, 2020)
Along with the times, literature, culture and society are growing steadily. The Three are affected by the speed of movement conditions of social life in the development of modern society lifestyle. The importance of the revitalization process in literature basically is to restore the function of literary works against society. Its main purpose is to describe the influence learning strategy and the revitalization of the regional literary writing activities and reproduce literature. Thus it would be useful both theoretically and practically. It is directly enrich the regional literature as a form of Indonesian literature. The method used in this research is quasi-experimental method (quasi experiment). This study is called an unreal experiment, or also called a mock experiment. After conducting research with the strategy, there are 31 works of literature revitalized through folklore and regional stories that exist in Indonesia. The work then became one and a book entitled Reproduction of Regional Literature R5A. From the experimental results, the groups can be concluded that there is an average score between the experimental group and the control group. Known after consultation on table turns out significant number.